2013
DOI: 10.1038/hdy.2013.32
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the effects of mating systems and mutation rates on cytoplamic diversity in gynodioecious Silene nutans and dioecious Silene otites

Abstract: Many flowering plant species exhibit a variety of distinct sexual morphs, the two most common cases being the co-occurrence of females and males (dioecy) or the co-occurrence of hermaphrodites and females (gynodioecy). In this study, we compared DNA sequence variability of the three genomes (nuclear, mitochondrial and chloroplastic) of a gynodioecious species, Silene nutans, with that of a closely related dioecious species, Silene otites. In the light of theoretical models, we expect cytoplasmic diversity to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…This breeding system gives rise to genomic conflict between cytoplasmic male sterility factors and nuclear restorers of fertility (Saumitou-Laprade et al 1994;Garraud et al 2011). Previous studies on S. nutans have suggested that gynodioecy is under balancing selection, thus enabling the maintenance of cytoplasmic genomes for a long period of time that could ultimately accumulate mutations genetically linked to the sterilizing gene (Touzet and Delph 2009;Lahiani et al 2013). But genetic incompatibilities should not be necessarily directly involved in male sterility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This breeding system gives rise to genomic conflict between cytoplasmic male sterility factors and nuclear restorers of fertility (Saumitou-Laprade et al 1994;Garraud et al 2011). Previous studies on S. nutans have suggested that gynodioecy is under balancing selection, thus enabling the maintenance of cytoplasmic genomes for a long period of time that could ultimately accumulate mutations genetically linked to the sterilizing gene (Touzet and Delph 2009;Lahiani et al 2013). But genetic incompatibilities should not be necessarily directly involved in male sterility.…”
Section: Discussionmentioning
confidence: 99%
“…An individual's assignment to W1 or E1 plastid groups was based on a combination of six plastid SNPs developed from the intergenic spacer sequences psbA-trnH and the matK gene fragment of S. nutans representative samples (Lahiani et al 2013) and described in Martin et al (2016). An individual's assignment to W1 or E1 plastid groups was based on a combination of six plastid SNPs developed from the intergenic spacer sequences psbA-trnH and the matK gene fragment of S. nutans representative samples (Lahiani et al 2013) and described in Martin et al (2016).…”
Section: Molecular Markersmentioning
confidence: 99%
“…A recent comparison of sequence variability between these three genomes in S. nutans and a closely related dioecious species, S. otites , found more haplotypes and more nucleotide diversity in the two cytoplasmic genomes of the gynodioecious species, but no difference for nuclear gene diversity between the species (Lahiani et al ., 2013). This result was found in spite of a likely higher rate of mitochondrial mutations in the dioecious species, discounting mutation rate differences as being responsible, and supporting the conclusion that balancing selection was operating.…”
Section: Balanced Polymorphisms Within Plant Speciesmentioning
confidence: 99%
“…Plastid diversity was investigated using SNPs recently developed from plastid sequences (pDNA) of S. nutans representative samples (Lahiani et al, 2013). Plastid SNPs were defined based on six polymorphic pDNA nucleotides in the intergenic spacer sequences psbA-trnH, named Cp 42, and the matK gene fragment, named Cp 397, Cp 540, Cp 656, Cp 730 and Cp 804.…”
Section: Molecular Analysesmentioning
confidence: 99%